Influence of Organizational Culture and Transformational Leadership on Employee Performance through Job Satisfaction as an Intervening - Pratama, R. Dandy Jurindra; Tridayanti, Hermien; Suyono, Joko; Sumarno, Sumarno; Salamin, Akhmad Lutfis (INNOVATION RESEARCH JOURNAL, 2025)
his study examines the influence of organizational culture and transformational leadership on employeeperformance, with job satisfaction as an intervening variable, at Dinas Sumber Daya Air dan Bina MargaSurabaya. The research focuses on 176 permanent employees using saturated sampling, where theentire population is included. Data were collected through direct questionnaires, allowing respondents toprovide feedback, and were analyzed using path analysis with multiple linear regression in SPSS version17.0. The results indicate that both organizational culture and transformational leadership positivelyimpact job satisfaction and employee performance. However, job satisfaction mediates the effect oftransformational leadership on performance but not the effect of organizational culture. The studyhighlights the importance of fostering a dynamic learning culture to improve job satisfaction andperformance. It suggests the Surabaya City Government continue focusing on these factors to enhanceoverall organizational outcomes.